Advanced Composite Lithium Metal Anodes with 3D Frameworks: Preloading Strategies, Interfacial Optimization, and Perspectives. Issue 10 (14th December 2022) - Cao, Jiaqi; Qian, Guoyu; Lu, Xueyi; Lu, Xia
Abstract: Lithium (Li) metal is regarded as the most promising anode candidate for next‐generation rechargeable storage systems due to its impeccable capacity and the lowest electrochemical potential. Nevertheless, the irregular dendritic Li, unstable interface, and infinite volume change, which are the intrinsic drawbacks rooted in Li metal, give a seriously negative effect on the practical commercialization for Li metal batteries. Among the numerous optimization strategies, designing a 3D framework with high specific surface area and sufficient space is a convincing way out to ameliorate the above issues. Due to the Li‐free property of the 3D framework, a Li preloading process is necessary before the 3D framework that matches with the electrolyte and cathode. How to achieve homogeneous integration with Li and 3D framework is essential to determine the electrochemical performance of Li metal anode. Herein, this review overviews the recent general fabrication methods of 3D framework‐based composite Li metal anode, including electrodeposition, molten Li infusion, and pressure‐derived fabrication, with the focus on the underlying mechanism, design criteria, and interfacial optimization. These results can give specific perspectives for future Li metal batteries with thin thickness, low N/P ratio, lean electrolyte, and high energy density (>350 Wh Kg −1 ). Abstract : 3D framework is the advanced component to realize the high‐performance lithium metal anode. This review focuses on the most recent lithium preloading and interfacial optimization strategies for 3D framework‐based composite lithium metal anode. The valuable but neglected aspects in the design of 3D frameworks are highlighted, expecting to give enlightened guidance for the practical application of lithium metal anode.